Presença do sagrado na música caipira de raiz brasileira: análise de composições de Tião Carreiro e Pardinho - Gregolim Junior, Luiz Manoel (2011)
This dissertation examines the Presence of the Sacred in Brazilian Country Roots Music mainly focused on songs of the duo Tião Carreiro and Pardinho. By this way, a historical study of hillbilly music, hillbilly traditions and hillbilly culture is done. Through the same historical perspective is carried out a research on the life and work of the duo Tiao Carreiro and Pardinho, and finally analyzes the presence of the sacred in its music and in other duo artists music. With this dissertation, we attempt to observe the religious expression found in Brazilian country roots music, but also other religious events found in the music of the highlighted duo. In regard to the presence of sacred in songs the difference from this duo to the others duo artists is the fact that its songs contain other manifestations of religiosity beyond Brazilian popular catholicism.